2021
DOI: 10.1128/mbio.03141-20
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin Biosynthesis Is Essential for Phagocytic Signaling during Mycobacterium tuberculosis Host Cell Entry

Abstract: Phagocytosis by alveolar macrophages is the obligate first step in Mycobacterium tuberculosis (Mtb) infection, yet the mechanism underlying this process is incompletely understood. Here, we show that Mtb invasion relies on an intact sphingolipid biosynthetic pathway. Inhibition or knockout of early sphingolipid biosynthetic enzymes greatly reduces Mtb uptake across multiple phagocytic cell types without affecting other forms of endocytosis. While the phagocytic receptor dectin-1 undergoes normal clustering at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Similarly, we and others demonstrate that sphingolipid biosynthesis is essential for phagocytic uptake and clearance of C. albicans and other microbial pathogens [38][39][40][41]. In particular, we demonstrated evidence that sphingolipid biosynthesis is essential for formation of the phagocytic synapse upon contact with Zymosan A, a model particle for fungal cells composed of β-1,3-glucans.…”
Section: Phagocytosis: the Weapon Of Choicesupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, we and others demonstrate that sphingolipid biosynthesis is essential for phagocytic uptake and clearance of C. albicans and other microbial pathogens [38][39][40][41]. In particular, we demonstrated evidence that sphingolipid biosynthesis is essential for formation of the phagocytic synapse upon contact with Zymosan A, a model particle for fungal cells composed of β-1,3-glucans.…”
Section: Phagocytosis: the Weapon Of Choicesupporting
confidence: 77%
“…In particular, we demonstrated evidence that sphingolipid biosynthesis is essential for formation of the phagocytic synapse upon contact with Zymosan A, a model particle for fungal cells composed of β-1,3-glucans. In sphingolipid-deficient cells, we observe that the phagocytic receptor Dectin-1 and the anti-phagocytic phosphatase CD45 remain colocalized at the contact site [39]. Thus, membrane order and composition at the phagosomal synapse have significant influences on the clearance of fungal pathogens.…”
Section: Phagocytosis: the Weapon Of Choicementioning
confidence: 89%
“…Mononuclear phagocytes rely on membrane remodelling during phagocytosis and endo‐lysosomal trafficking for eliminating pathogens and process/present antigens. Phagocytosis of pathogens, lysosomal stability, vesicular fusion, receptor‐mediated chemotaxis, autophagy and antigen presentation are all dependent on sphingolipid metabolism (Denard et al, 2019; Jongsma et al, 2021; Kirkegaard et al, 2010; Niekamp et al, 2021; Sims et al, 2010; Utermohlen et al, 2008). Notably, sphingolipids also regulate the TLR4‐mediated innate immune response in macrophages (Koberlin et al, 2015).…”
Section: Sphingolipids and Macrophage Effector Functionsmentioning
confidence: 99%
“…Recently, genome-wide CRISPR screening showed that the enzymes ceramide synthase, fatty acid elongase and sphingomyelin synthase 1 (SMS1) are involved in phagocytosis [173]. In addition, sphingomyelin biosynthesis was reported to be critical for the uptake of M. tuberculosis by human macrophages [174]. Quantitative lipidomic analysis demonstrated that ceramide synthase 2 (CerS2) is enriched in early phagosomes and that the amounts of C24 ceramides are increased in late phagosomes [175].…”
Section: Intracellular Interactions Between Gsl-enriched Microdomains and Pathogensmentioning
confidence: 99%